A prospective study to evaluate the impact and independency of depth of invasion in comparison with other clinicopathologic prognostic variables in oral cavity malignancy - Shanmugam, Subbiah; Govindasamy, Gopu; Raja, X. Gerald Anand (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Depth of invasion is included in the staging of oral cavity malignancies in the recent 8th edition of American Joint Committee on Cancer or tumour, node and metastasis staging system. This study analyses the impact of diffuse optical imaging (DOI) on incidence of lymph node involvement, stage migration, postoperative margin and independency. Methods: Postoperative HPE of fifty patients with oral cavity malignancy operated in our institute from January 2018 were collected. Depth of invasion and other pathological parameters were documented. DOI divided into three groups and statistical analysis done. Results: No lymph node metastasis is found in superficial tumours, 43% of intermediate thickness and 76% of deep tumours had lymph node involvement. Positive margin is seen only in patients with tumour DOI more than 0.5 cm, more than 50% of deep tumours had close margins while 75% of superficial tumours had adequate margin. Out of the 24 T3 tumours in this study 13 were upstaged due to inclusion of DOI, which would have been T2 according to the previous staging system. There is 54.1% (13 out of 24) upstaging in T3 tumours (T2 to T3), 23% (3 out of 13) in T2 (T1 to T2). There is no significant correlation between DOI and anatomical site, tumour size, tumour thickness, lymphovascular invasion and grade. Conclusions: Depth of invasion in oral cavity malignancies impacts adversely lymph node metastasis and margin status. It is an independent prognostic factor in oral cavity malignancy.